AN ANALYSIS OF THE VERBAL COMMUNICATION OF PEER COUNSELORS IN PERFORMING ONLINE COUNSELING SERVICES - Meliyawati Melitawati; Ajeng Muliasari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study focused on an analysis of the verbal communication of peer counselors in performing online counseling services in the pandemic phase in Indonesia. This study utilized a qualitative research approach with analytical decriptive, referring to a method to obtain a view sistematically, factually, and accurately related to the facts and properties of the objects into which the research focused. Then, the results of the finding were analyzed and interpreted to draw conclusions. The online peer counseling services were performed by students of BK UNMA for 2 weeks. The services were available by using some social media. The online peer counseling services focused on interpersonal communication processes through communication channels. Results indicated that in performing online counseling services, the counselors used several verbal communication techniques, such as invitations to start, reception/showing understanding, reflection of mind, reflection of feelings, clarifications of messages, feedback, alternative presentations, inquiries, interpretations, diagnosis, supports/guidance, and suggestion. These techniques were performed based on the dominant issues the clients faced, which were related to self-confidence/insecure, and family and employment problems.